A pathway-specific function for different AMPA receptor subunits in amygdala long-term potentiation and fear conditioning. - Humeau, Y; Reisel, D; Johnson, A; Borchardt, T; Jensen, V; Gebhardt, C; Bosch, V; Gass, P; Bannerman, D; Good, M; Hvalby, Ø; Sprengel, R; et al. (2007)
The AMPA receptor subunit glutamate receptor 1 (GluR1 or GluR-A) contributes to amygdala-dependent emotional learning. It remains unclear, however, to what extent different amygdala pathways depend on GluR1, or other AMPA receptor subunits, for proper synaptic transmission and plasticity, and whether GluR1-dependent long-term potentiation (LTP) is necessary for auditory and contextual fear conditioning. Here, we dissected the role of GluR1 and GluR3 (GluR-C) subunits in AMPA receptor-dependent amygdala LTP and fear conditioning using knock-out mice (GluR1-/- and GluR3-/-). We found that, whereas LTP at thalamic inputs to lateral amygdala (LA) projection neurons and at glutamatergic synapses in the basal amygdala was completely absent in GluR1-/- mice, both GluR1 and GluR3 contributed to LTP in the cortico-LA pathway. Because both auditory and contextual fear conditioning were selectively impaired in GluR1-/- but not GluR3-/- mice, we conclude that GluR1-dependent synaptic plasticity is the dominant form of LTP underlying the acquisition of auditory and contextual fear conditioning, and that plasticity in distinct amygdala pathways differentially contributes to aversive conditioning.